Incidental hepatic tuberculosis during planned resection of locally advanced ampullary carcinoma: a case report - Vee Chuan Hoe; Allim Khairuddin; Jun Sam Tan; Mohd Sharifudin Sharif; Nornazirah Azizan; Firdaus Hayati (2020)
Background: Tuberculosis (TB) is classified according to the site of disease as pulmonary or extrapulmonary. Extrapulmonary TB is less common than its counterpart in which it can be found anywhere in the body including the liver. Similar to ampullary carcinoma, TB liver can manifest with jaundice and deranged liver function tests, particularly in the obstructed biliary systems. Case presentation: A 43-year-old gentleman with locally advanced ampullary carcinoma was noticed to have multiple suspicious liver nodules intraoperatively during curative ampulla resection. The surgery was then abandoned after a biopsy. The histology was consistent with chronic granulomatous inflammation. He was then subjected to a Whipple pancreaticoduodenectomy procedure after initiation of anti-tubercular treatment. He recovered well with no evidence of tumour recurrence and worsening TB. Conclusions: A high index of suspicion and quick decision making can help to diagnose a possible extrapulmonary TB masquerading as a malignant disease in a patient with curative intention of ampullary carcinoma.